(untitled) (International Seven Journal of Health Research, 2023)
It is known that resistance training for women brings several benefits such as improved health, physical and emotional well-being, and improved strength capacity, and can also help in the menstrual cycle. Most women believe that menstrual symptoms such as weight gain, cramps, bloating, and discouragement are factors for the loss of muscle performance; however, regular and periodized training according to the biological individuality can minimize these symptoms. The objective of the study was to carry out a bibliographic review about the influence of the phases of the menstrual cycle on the strength capacity in resistance training. Consultations were made to the following databases: Scielo, Medline, Lilacs, and Pubmed, using the following criteria: date of publication between January 2000 and December 2019; languages, Portuguese and English; terms included in the title and/or abstract - woman, strength training, menstrual cycle, resistance exercise, strength levels, and effects of the phases of the menstrual cycle on resistance training. Eight studies were analyzed, where four observed menstrual cycle interferences on strength performance and four did not. Thus, it can be concluded that the relationship of strength during the phases of the menstrual cycle are still controversial. It is suggested that further studies be carried out to verify and prove the influence of the phases of the menstrual cycle on strength capacity in resistance training.